Própolis e monensina sódica em dietas volumosas sobre a digestibilidade e características ruminais de bovídeos - Prado, Odimári Pricila Pires do (2008)
The objective was to evaluated a propolis based product (LLOS) patented (PI No 0605768-3) which consist of dried extract of propolis ranging in alcohol extraction (1, 2 and 3) and propolis concentration (A, B, C and D ): LLOSC1, LLOSD1, LLOSA2, LLOSB3, LLOSC3, on the biochemical and morphological characterization of isolated bacteria tolerant to products LLOSC1, LLOSB3 in diets with 100% roughage and products LLOSC1, LLOSD1, LLOSA2, LLOSC3 in diets 50% roughage and 50% concentrate and administration of products LLOSB3 and LLOSC1 compared with monensin sodium on intake and total and partial digestibility of dry matter and nutrients, characteristics and rumen microbial efficiency in cattle and buffaloes fed diets based on 80% of roughage. In diets with 100% roughage it was found that the strains tolerant to LLOSC1 were higher in ferment cellobyose (92.4 vs. 78.3%) and cellulose (57.7 vs. 34.8%) compared with strains resistant to LLOSB3 which presented as more specialists. For diet 50:50, roughage:concentrate, it was highlight the product LLOSC3 followed by LLOSA2 that selected a larger number of generalists strains that use the different evaluated carbohydrates: arabinose, cellulose, glucose, celobiose, xylose, fructose, lactose. The product LLOSA2 selected strains that grew until 6:30 h, the others products selected strains that had growth rates ranging from 6:30 to 37:00 h . It was used four Holstein cattle and four Murrah buffaloes in an experimental design Latin square 4 x 4 (4 diets: control, monensin, LLOSC1 and LLOSB3 and 4 periods, for each species). The diets given to cattle roughage containing 72.5% and 27.5% of concentrate, with 14.4% CP and 67% of TDN and buffaloes had given to 80% of roughage and 20% concentrate, with 11. 1% of CP and 66% of TDN. The intake of DM and other nutrients did not differ between the experimental diets, as for buffalo and cattle, except for the TDN intake in cattle that was higher (P<0.05) for control diet than the others one. The cattle diet control was higher (P<0.05) in total digestibility (TD) of DM and nutrients. Among the additives tested the monensin influenced negatively the TD of DM, OM, CP than diets containing LLOSC1 and LLOSB3 (P<0.05). The ruminal digestibility (% of total digested) of DM, NDF, ADF and CHT was positively influenced (P<0.05) by monensin sodium and LLOSB3 in relation to control diets and xix LLOSC1 l and the reverse was observed in intestinal digestibility (ID). There was effect of diet on the ruminal pH in cattle and concentrations of total VFA, acetate and relationship acetate:propionate. The highest ruminal pH highest and lowest ratio acetate: propionate (P<0.05) was observed for monensin sodium diet and LLOSC1 and LLOSB3 showed higher production of acetate and total VFA. There was an increase in the volume rumen for diets LLOSC1 and LLOSB3 (59.5 and 62.2 L, respectively) compared with the control diet (50.5 L) and there was no effect of diet on the efficiency of microbial synthesis in cattle. For the addition of buffalo LLOSC1 provided higher (P<0.05) total digestibility coefficients (TD) in relation to the control for DM (62.8% vs 59.4%), NDF (58.6% vs. 54.3%), CHT (65.1% vs 61.5%) and NDT (65.8 vs. 62.3%), and monensin diet was similar to the control. The ruminal digestibility (% of total digested) of DM, NDF, ADF and CHT were higher control in relation to diet and the other was the lowest values for LLOSC1 diet. Minor rumen absorption of ammonia N (lower value of the CP RD) and higher rates of ID of CP and the NSC was observed for LLOSC1 diet in relation to the control. There was effect (P<0.05), time of collection after feeding on pH, NH3-N and VFA. The diet had lower LLOSB3 value of ruminal pH (6.48) and increased production of butyrate (7.94 ?M/mL) (P<0.05) and trend of increased production of acetate (P<0.07) compared the other. The passage rate of liquid did not differ (P>0.05) between the diets, but there was a tendency for greater volume rumen (P<0.08) to diets containing additives regarding control. The propolis based additive LLOSC1 had the highest efficiency of microbial synthesis (36.6 g N-Mic/kg OMDR) in relation to the control (25.8 g N-Mic/kg OMDR). Thus, it was concluded that the bacteria strains tolerant to the propolis based products were more generalists and specialists in the degradation of different evaluated substrates depending on the used LLOS product and type of diet, it is not recommended the use of monensin sodium and propolis based products based on diets based on roughage for cattle in growth, but it is recommended the use of the LLOSC1 product in buffaloes fed with bulky diets.